Effect of cold water immersion after exercise in the heat on muscle function, body temperatures, and vessel diameter - Peiffer, J. J.; Abbiss, C. R.; Nosaka, K.; Peake, J. M.; Laursen, P. B. (Journal of Science and Medicine in Sport, 2009)
Cold water immersion (CWI) is a popular recovery modality, but actual physiological responses to CWI after exercise in the heat have not been well documented. The purpose of this study was to examine effects of 20-min CWI (14 °C) on neuromuscular function, rectal (Tre) and skin temperature (Tsk), and femoral venous diameter after exercise in the heat. Ten well-trained male cyclists completed two bouts of exercise consisting of 90-min cycling at a constant power output (216 ± 12 W) followed by a 16.1 km time trial (TT) in the heat (32 °C). Twenty-five minutes post-TT, participants were assigned to either CWI or control (CON) recovery conditions in a counterbalanced order. Tre and Tsk were recorded continuously, and maximal voluntary isometric contraction torque of the knee extensors (MVIC), MVIC with superimposed electrical stimulation (SMVIC), and femoral venous diameters were measured prior to exercise, 0, 45, and 90 min post-TT. Tre was significantly lower in CWI beginning 50 min post-TT compared with CON, and Tsk was significantly lower in CWI beginning 25 min post-TT compared with CON. Decreases in MVIC, and SMVIC torque after the TT were significantly greater for CWI compared with CON; differences persisted 90 min post-TT. Femoral vein diameter was approximately 9% smaller for CWI compared with CON at 45 min post-TT. These results suggest that CWI decreases Tre, but has a negative effect on neuromuscular function.